Using European Option Contracts in the Taxation of the Indicators of the Stocks. Applied Study for the General Indicator of the Iraq Market for Securities (ISX60) - Hameed Al-Dahaan, Noor Sabah; Abid Al-Shara, Aqeel Shakir (Opción, 2019)
The study aims to discover how to achieve the best financial returns in the shade of fluctuations that are happening in the level of the prices in the financial mar- kets, and this represents the marketing risky factor. However, the indicators of the stocks will not be an ideal financial tool to get rid from the problems of these risks. Therefore, it is necessary to invent modern and developed financial tools that can overcome price fluctuations which happen in the financial markets like financial derivatives. This means that the using of these tools like contracts of the options and indicators of the stocks which are requiring mathematical sample to put price for them. Thus, the European style is getting its price according to the (Black – Sholes) sample which is characterized with its finite preciseness in taxation the contracts of the European options on the indicators of the stocks in the two cases of selling and buying. This study depends on the quarterly closing prices of the general indicator of the market (ISX60) in the Iraq market for the securities from the period 1/ January/2015 to 31/December/ 2017 by using some of the statistical, financial, and mathematical samples. Therefore, this study reached to several con- clusions, the most important one is that the (Black- Sholes) sample is a very precise sample in imaging the process of taxation the contracts of the European options, and this is confirming the whole extracted results in applying the taxation of the contracts of the options of the stocks.This study recommends that it is necessary to depend on the (Black-Sholes) sample in taxation the contracts of European options on the indicators of the stocks in the Iraq market for the securities due to its qualification and its preciseness in taxation these contracts.